Pengembangan Interaktif Mobile Learning untuk Meningkatkan Kemampuan Numerasi Siswa Kelas V SD - Aini, Qurrotul (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to develop constructivist-based interactive mobile learning as a learning medium in mathematics in class V on simple fractions. The research method used is research development or R&D (Research and Development) with the 4-D model (Define, Design, Development, and Disseminate) chosen. In this study, using research subjects of class IV students at SDN Sawohan 1 with a total of 19 students. Analysis of the data used in the form of descriptive analysis. Data collection techniques used observation, tests (pretest and posttest), validation questionnaires (validation of media experts, material expert validation, teacher responses, and student responses), and documentation. The results showed that interactive mobile learning was stated to be very feasible or valid, with a score obtained from material experts of 95% and media experts of 85%. In its use, interactive mobile learning gets a very good response from teachers and students with a score on the practicality test of the teacher’s response of 95,66% which is stated to be very practical. The results for student responses found a score of 91% which can be said to be interactive mobile learning attractive to students. This certainly has an impact on students’ understanding of simple fraction material with an average pretest score of 83.3 and 90.5 posttest. So interactive mobile learning can help students learn mathematics in elementary schools.